2013
DOI: 10.3892/ijmm.2013.1514
|View full text |Cite
|
Sign up to set email alerts
|

Low doses of ionizing radiation induce immune-stimulatory responses in isolated human primary monocytes

Abstract: Abstract. The health effects arising from exposure to low doses of ionizing radiation are of particular concern, mainly due to the increased application of diagnostic and therapeutic X-ray modalities. The mechanisms behind the cell and tissue responses to low doses remain to be elucidated. Accumulating evidence suggests that low doses of ionizing radiation induce activation of the immune response; however, the processes involved have yet to be adequately investigated. Monocytes are key players in the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 45 publications
5
38
0
Order By: Relevance
“…12). Other investigators have reported similar observations in human monocytes treated with purified HMGB1 (32,68). Monocytes and macrophages are the key players in orchestrating the immune response to infection and injury.…”
Section: Fig 11supporting
confidence: 62%
“…12). Other investigators have reported similar observations in human monocytes treated with purified HMGB1 (32,68). Monocytes and macrophages are the key players in orchestrating the immune response to infection and injury.…”
Section: Fig 11supporting
confidence: 62%
“…The authors of previous research have reported that cardiovascular morbidity and mortality may occur decades after ionizing radiation exposure (Yan et al, 2014). The health risks arising from exposure to low doses of ionizing radiation should be re-evaluated (El-Saghire et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The health risks arising from exposure to low doses of IR have been identified in previous studies (Kamiya et al, 2015), and should be re-evaluated (El-Saghire et al, 2013). The incidences of cataracts are closely associated with IR exposure (Shore et al, 2010;Kleiman, 2012).…”
Section: Discussionmentioning
confidence: 92%